A Cross Cultural Test of Financial Risk Tolerance Attitudes: Brazilian and American Similarities and Differences - N. Nobre, Liana Holanda; Grable, John E.; Da Silva, Wesley Vieira; Da Veiga, Claudimar Pereira (International Journal of Economics and Financial Issues, 2016)
The purpose of this study was to examine the extent to which risk-tolerance attitudes differ between a sample of Brazilians and Americans (N = 620). Based on the use of a variety of statistical methodologies, including regression, factor, and discriminant analysis. The results indicate that Americans were more apt to engage in a speculative gamble and they were less likely to hold bonds as a safe asset. Overall, both Brazilian and American female respondents exhibited lower risk-tolerance scores; however, no age or marital status differences were noted. The results from this analysis show that cultural differences exist between Brazilians and Americans in terms of financial risk-tolerance attitudes. Keywords: Risk tolerance; Cross cultural; Financial risk. JEL Classifications: G1, M1